Faktor-Faktor yang Dipertimbangkan Pelanggan Untuk Mengambil Keputusan Melakukan Perawatan Mobil di PT. Agung Automall Denpasar - Chrisnadewi, Ni Made Ayu Sukma; Suasana, I Gst. A Kt. Gd (E-Jurnal Manajemen, 2013)
The purpose of this study was to determine the factors that consumers consider the decision to perform maintenance PT Agung Automall car in Denpasar. This research was conducted at PT Agung Automall Denpasar with a sample of 150 people using accidental sampling technique. By using Principal Component Analysis (PCA), obtained seven factors that customers consider are: (1) socio-cultural factors with the psychological factor loading of 0.718. (2) product and pricing factors with loading factor of 0.699. (3) factors and the promotion of the loading factor of 0.714. (4) physical evidence factor with factor loading of 0.661. (5) Factor loading process with a factor of 0.756. (6) distribution factors with loading factor of 0.826 (7) personal factor with factor loading of 0.824. Suggestions that can be recommended is expanded parking for customers so that customers feel comfortable. Keywords: Factors, Consumer, Decision, Car Care